Evidence from population mixing in British New Towns 1946-85 of an infective basis for childhood leukaemia. - Kinlen, L; Clarke, K; Hudson, C (1990)
Mortality from leukaemia under age 25 was studied in British New Towns to test the hypothesis that leukaemia represents a rare response to a much commoner (but unrecognised) infection, the transmission of which is facilitated when large numbers of people come together. The density of children was higher in the rural, but lower in the overspill, New Towns than in the areas from which their incomers originated. Residents of the rural New Towns had greater diversity of origin than those of the overspill towns of London and Glasgow. These two factors would encourage a greater rise in the postulated underlying infection in the rural towns, and in these a significant excess of leukaemia at ages 0-4 was found in 1946-65. In both sets of towns there was a significant deficit in other age groups consistent with immunising effects of the relevant infection. There are parallels with feline leukaemia virus infection, in which contrasting leukaemogenic and immunising effects occur in different social settings owing mainly to differences in intensity of viral exposure.